Implementasi Model Problem Based Learning Berbantuan Media Puzzle Angka untuk Meningkatkan Hasil Belajar Matematika Peserta Didik Kelas 2 SD: Penelitian Tindakan Kelas (PTK) - Wahyuni, Nini; Sukmawati, Sukmawati; Wahyudi, Andi Ardhila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to improve the learning outcomes of class 2A students through the implementation of the problem based learning model assisted by number puzzle media at UPT SPF SD Inpres Pa'baeng-baeng 1. The type of research used was Classroom Action Research (CAR), which consisted of 2 cycles. Where each cycle consists of 4 meetings carrying out the learning process with research stages, namely planning, implementation, observation and reflection. The subjects of this study were 29 class 2A students. Data collection from the research results was in the form of observation formats, evaluation tests and documentation. The data analysis techniques used were quantitative and qualitative. The results showed that there was an increase in mathematics learning both in teacher teaching activities and student learning activities. Furthermore, the conclusion of this study is that in learning activities students are more active in following a learning when compared between cycle I to Cycle II and attract more student attention by implementing the PBL model assisted by number puzzle media. This is proven based on the results of the evaluation test, there was an increase from cycle I, where a score of 69% was obtained in the sufficient category, which increased in cycle II, where a score of 92% was obtained in the very good category and the implementation of the problem-based learning model assisted by number puzzle media can improve the Mathematics learning outcomes of class 2A students.